Alkaan Speil Game: Encouraging Higher-Order Thinking in Alkane Learning Material - Erlangga Yoga Perdana; Neneng Windayani; Ferli Septi Irwansyah (Online Learning In Educational Research (OLER), 2023)
This research aims to describe and analyze the validation and feasibility of the Alkaan Speil game interface. The method used in this study is design-based research (DBR), which encompasses three stages: analysis, design, and development. The validation test results yielded a calculated r-value of 0.93, indicating a high level of validity. Furthermore, the feasibility test, which includes content and material aspects, software engineering, and audio-visuals, resulted in a percentage of 84.08, suggesting that the Alkaan Speil game is effective as a learning tool for alkane material with a higher-order thinking approach. The findings of this research present significant implications for educational technology and pedagogy. The high validity score of 0.93 for the Alkaan Speil game underscores its robust design and affirms its potential as an innovative educational tool. The feasibility test results, with an impressive 84.08 score, further reinforce the game's effectiveness in facilitating higher-order thinking skills in the context of learning alkanes. This underlines the game's capacity to enhance understanding and engagement in chemistry education. While the current study was confined to the application's development phase, the implications extend to the need for comprehensive testing of the game's efficacy in a real-world educational setting. Future research should focus on deploying the game in classroom environments to empirically assess its impact on learning outcomes and student engagement, thereby contributing to the broader knowledge base of educational strategies in science teaching.